A rare presentation of antenatally diagnosed Wilms tumor: A case report - Pradeep Kajal; Namita Bhutani; Bhaswati Bharadwaj (EL-Med-Pub, 2024)
Background: Wilms' tumor is the most common renal malignancy in children, with a peak incidence between 1 and 4 years of age. The prevalence of antenatal renal tumors is scarce, around 7 in 100,000 live births. We report a case of an antenatally diagnosed Wilms tumor. Case Presentation: A 2-month-old infant presented with a right renal lump since birth. The antenatal USG done at 35 weeks of gestation, showed an ill-defined heteroechoic area of size 57.3X29.9 mm at the upper pole of the right kidney, with few cystic areas with increased echogenicity. A right nephroureterectomy was done. It was WT1 and Vimentin positive and focally positive for Cyclin D1, whereas negative for Desmin, SMA, and PAX8, thus confirming the histopathological diagnosis of Wilms' tumor. Conclusion: Antenatal Wilms' tumor is rarely detected. A high degree of suspicion and active investigations should be conducted in antenatal and immediate neonatal periods for prompt decision-making and better outcomes.